2020
DOI: 10.1111/acps.13229
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents’ knowledge of a peer's non‐suicidal self‐injury and own non‐suicidal self‐injury and suicidality

Abstract: Objective Some research suggests that suicidal ideation and attempt among adolescents may be contagious – that is adolescents who are exposed to peers’ suicidal behaviour are more likely to experience suicidal ideation or attempt suicide themselves. Less is known about the potential contagion effect of non‐suicidal self‐injury (NSSI). Our objective was to determine whether knowledge of a friend's NSSI is associated with adolescent's own non‐suicidal self‐injury and suicidal behaviours. Methods Data from 1483 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 44 publications
(55 reference statements)
3
7
0
3
Order By: Relevance
“…Therefore, depression is a possible explanatory mechanism that might explain why adolescents with deviant peer affiliation are more likely to engage in NSSI. Our results are consistent with those of other studies that have reported that deviant peer affiliation and depression increased the risk of engaging NSSI [17,21]. Depression has also been found to mediate the relationship between peer acceptance and NSSI [22].…”
Section: The Mediating Role Of Depressionsupporting
confidence: 93%
See 3 more Smart Citations
“…Therefore, depression is a possible explanatory mechanism that might explain why adolescents with deviant peer affiliation are more likely to engage in NSSI. Our results are consistent with those of other studies that have reported that deviant peer affiliation and depression increased the risk of engaging NSSI [17,21]. Depression has also been found to mediate the relationship between peer acceptance and NSSI [22].…”
Section: The Mediating Role Of Depressionsupporting
confidence: 93%
“…Finally, in addition to finding evidence of both parts of the proposed mediation model, the results also showed that adolescent depression significantly mediated the link between deviant peer affiliation and NSSI. This finding further deepens and enriches the findings from a small number of studies that tested this association [16,17]. In addition, this research provides a basis for intervention to prevent and reduce adolescent NSSI.…”
Section: The Mediating Role Of Depressionsupporting
confidence: 67%
See 2 more Smart Citations
“…This applies especially to younger children (van Geel, Goemans, & Vedder, 2015) and bully-victims who have been rejected by their peers (Esposito et al, 2019). Further, there is some evidence that knowing a friend who engages in NSSI is associated with increased risk of engaging in NSSI (Hasking, Andrews, & Martin, 2013;Syed, Kingsbury, Bennett, Manion, & Colman, 2020). However, exposure to NSSI by peers in itself is not suficient to encourage an individual to self-injure (Hasking et al, 2013).…”
Section: Introductionmentioning
confidence: 99%